Heat Transfer Enhancement in Air Cooled Gas Turbine Blade Using Corrugated Passages. - Rashid, Farhan Lafta; Azziz, Haider Nadhom; Hussein, Emad Qasem (Journal of Petroleum Research and Studies, 2018)
In this paper, an investigation of using corrugated passages instead of circular cross section passages was achieved in conditions simulate the case in the gas turbine blade cooling using ANSYS Fluent version (14.5) with Boundary conditions: inlet coolant air temperature of 300 K with different air flow Reynolds numbers (191000, 286000 and 382000). The surrounding constant hot air temperatures was (1700 K). The numerical simulations was done by solving the governing equations (Continuity, Reynolds Averaging Navier-stokes and Energy equation) using (k-ε) model in three dimensions by using the FLUENT version (14.5). The present case was simulated by using corrugated passage of 3 m long, internal diameter of 0.3 m, 0.01 m groove height and wall thickness of 0.01 m, was compared with circular cross section pipe for the same length, diameter and thickness. The temperature, velocity distribution contours, cooling air temperature distribution, the inner wall surface temperature, and thermal performance factor at the two passages centerline are presented in this paper. The coolant air temperature at the corrugated passage centerline was higher than that for circular one by (12.3%), the temperature distribution for the inner wall surface for the corrugated passage is lower than circular one by (4.88 %). The coolant air flow velocity seems to be accelerated and decelerated through the corrugated passage, so it was shown that the thermal performance factor along the corrugated passage is larger than 1, this is due to the fact that the corrugated walls create turbulent conditions and increasing thermal surface area, and thus increasing heat transfer coefficient than the circular case.